Pengaruh Penggunaan Modul Praktikum KKPI dengan Pendekatan Inkuiri Terhadap Hasil Belajar (Studi Kasus : Kelas X Multimedia SMK N 1 Sawan) - Made Artika Winati Mapet; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study is aimed to determine (1) the effectof using lab module KKPI with an inquiry approach tolearning the results of class X students of SMK Negeri 1Multimedia Sawan, (2) students' response to theapplication of the experimental module KKPI inquiryapproach. This is a type of quasi-experimental study(quasi-experimental) research design Posttest-OnlyControl Group Design. The study population was a classX student of SMK Negeri 1 Sawan school year 2012/2013.As the sample in this study is the class of X 1 and XMultimedia Multimedia 2, amounting to 54 people.Multimedia 2 class X is used as an experimental class andX-class Multimedia 1 as a control. The data was collectedusing a multiple-choice test method to measure thecognitive and skills testing to measure psychomotordomains. Learning outcomes data were analyzed to testthe prerequisites which include normality test,homogeneity test and t-test. As for the response by usingthe questionnaire method. Based on the analysis of thedata obtained, the test of normality and homogeneity ofthe two groups of normally distributed and homogeneous.(1) student learning outcomes using experimental moduleKKPI with an inquiry approach has an average valuethat is higher than conventional instructional media, (2)the obtained results are very positive student response.